2007
DOI: 10.1002/mrd.20574
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adenosine monophosphate‐activated kinase activators on bovine oocyte nuclear maturation in vitro

Abstract: The purpose of this study was to examine the effects of an activator of AMPK (5-aminoimidazole-4-carboxamide 1-beta-D-ribofuranoside (AICAR)) on bovine oocyte nuclear maturation in vitro. After 7 hr of culture, AICAR (1 mM) significantly increased the percentages of cumulus-enclosed oocytes (CEO) and denuded oocytes (DO) remaining at the germinal vesicle stage. After 22 hr of culture, AICAR significantly reduced the percentage of CEO reaching metaphase II (MII). AICAR at 1.0 mM also increased the inhibitory ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 50 publications
4
49
0
4
Order By: Relevance
“…Accordingly, various analyses have shown that AMPK triggers GVBD in denuded or cumulus-enclosed oocytes of mice (Chen et al 2006, LaRosa & Downs 2006, Chen & Downs 2008. Alternatively, AMPK agonists can block GVBD in other cumulus-enclosed mammalian oocytes (Bilodeau-Goeseels et al 2007, Mayes et al 2007, Tosca et al 2007, although such blockage is apparently due to effects on follicle cells and/or to non-AMPK-mediated pathways (Mayes et al 2007, Tosca et al 2007, Bilodeau-Goeseels et al 2010. However, oocytes of nemertean worms lack follicle cells , and AMPK activations nevertheless inhibit nemertean GVBD (Stricker et al 2010a(Stricker et al , 2010b, indicating that intraoocytic AMPK can stimulate or block MPF activation in different animals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, various analyses have shown that AMPK triggers GVBD in denuded or cumulus-enclosed oocytes of mice (Chen et al 2006, LaRosa & Downs 2006, Chen & Downs 2008. Alternatively, AMPK agonists can block GVBD in other cumulus-enclosed mammalian oocytes (Bilodeau-Goeseels et al 2007, Mayes et al 2007, Tosca et al 2007, although such blockage is apparently due to effects on follicle cells and/or to non-AMPK-mediated pathways (Mayes et al 2007, Tosca et al 2007, Bilodeau-Goeseels et al 2010. However, oocytes of nemertean worms lack follicle cells , and AMPK activations nevertheless inhibit nemertean GVBD (Stricker et al 2010a(Stricker et al , 2010b, indicating that intraoocytic AMPK can stimulate or block MPF activation in different animals.…”
Section: Introductionmentioning
confidence: 99%
“…For example, recent studies of intraoocytic AMPK in mice have assessed the relationship between diabetes and AMPK-mediated targets in glucose metabolism (Ratchford et al 2007), the activation of AMPK by FSH and amphiregulin (Chen & Downs 2008), and the interconnections between AMPK and fatty acid oxidative pathways (Downs et al 2009). Moreover, how AMPK interacts with MAPK and other signals has been evaluated in oocytes of cows and pigs (Bilodeau-Goeseels et al 2007, Mayes et al 2007, Tosca et al 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to results obtained with mouse oocytes where AMPK activation led to meiotic resumption (see section 2.3), meiosis was inhibited when bovine oocytes were cultured with the AMPK activator 5'-aminoimidazole-4-carboxamide 1--D-ribofuranoside (AICAR, Bilodeau-Goeseels et al, 2007). The inhibitory effect of AICAR was observed in cumulusenclosed and denuded oocytes, was reversible, increased the inhibitory effect of the AC activator FSK, was dependent on its phosphorylation by adenosine kinase and was not due to increased cAMP levels or to increased purine nucleotide synthesis (Bilodeau-Goeseels et al, 2007).…”
Section: Role Of Ampk In the Control Of Bovine Oocyte Meiosismentioning
confidence: 79%
“…The inhibitory effect of AICAR was observed in cumulusenclosed and denuded oocytes, was reversible, increased the inhibitory effect of the AC activator FSK, was dependent on its phosphorylation by adenosine kinase and was not due to increased cAMP levels or to increased purine nucleotide synthesis (Bilodeau-Goeseels et al, 2007). Metformin [MET, one of the most widely used drugs for the treatment of type 2 diabetes and an AMPK activator (Zhou et al, 2001)], was also reported to inhibit GVBD in bovine CEO and DO by Bilodeau-Goeseels et al (2007). In a subsequent study, however, the AMPK inhibitor Compound C (CC) did not reverse the effect of AICAR and MET and even had a significant inhibitory effect itself on bovine oocyte meiosis (Bilodeau-Goeseels et al, 2011).…”
Section: Role Of Ampk In the Control Of Bovine Oocyte Meiosismentioning
confidence: 99%
“…In cattle, similar to the pig, pharmacological activation of AMPK blocked nuclear maturation of the oocyte (at prophase of the first meiotic division or at the germinal vesicle stage (Bilodeau-Goeseels et al, 2007;Tosca et al, 2007b), whereas in mice AMPK improved the resumption of meiosis by accelerating rupture of the nuclear membrane (Bilodeau-Goeseels, 2011) or breakdown of the germinal vesicle (Downs and Chen, 2006). Although there are some differences among species, AMPK appears to be important for the breakdown of the germinal vesicle during nuclear maturation of the oocyte.…”
Section: Metabolic Hormonesmentioning
confidence: 99%